Manunggaling Kala Desa Melintas Fenomena Ruang Dan Waktu Dalam Penciptaan Seni Lukis - I Wayan Setem (Mudra Jurnal Seni Budaya, 2009)
Having observed and studied lingga-yoni, I have got an idea about “The Unity of Time-Space, Crossing the Phenomena of Time and Space in the Creation of Painting is the theme of my Works. What I would like to analyze here is the psycho- anthropological aspects of lingga-yoni. Hopefully this analysis is viewed as an effort to reread reinterpret the symbol of lingga- yoni in my paintings. My perception of lingga-yoni related to the unity of time-space is not merely understood as a sensing quality but as a self projection of various values involving new interpretations. I can perceive the significance of lingga-yoni so that I am fully aware of its relationship with time and space. This perception is related not only to the cognitive achievement but also to the feelings of various values such as aesthetical, moral, and religious. Thus in this context, I place the creative exploration in the painting creation as a critical reflection crossing the time and space phenomena with the theme of “Manunggaling Kala- Desa” (the unity of time-space).